PENGARUH PEMBELAJARAN EFEKTIF MELALUI MENGGUBAH LIRIK LAGU DAN BERYANYI UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN - Hanita Hanita; Mahkamah Brantasari (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2019)
Learning will be effective if experience, materials, and results are expected to be in accordancewith the maturity level of students and their backgrounds. Children's songs at this time become arare thing. Most children are now more familiar with adult songs. Adult songs are as complexand as long as any child can memorize. Music stimulation is one of the efforts of parents tooptimize the intelligence of the child. Singing activity is one of the activities that can be veryfavored by early childhood because singing children feel happy. especially for children, musiccan also improve speech, hearing confidence. Singing activities have a very big influence inhoning children's cognitive abilities, especially in remembering and thinking. The type of methodused in this study is experimental research. This experimental study uses a SPSS calculation tool(Statistical Product and Service Solutions) in the form of correlation and regression analysis.SPSS calculations are used to make it easier and an analyst solution to the prediction ofstatistical analysis. The population in this study were all children aged 4-6 years in one PAUDinstitution in Samarinda. The sample in this study used a purposive sampling technique. Datacollection techniques use observation techniques. The results obtained are Based on thereliability statistics table on the SPSS output above, obtained the cornbach's alpha value of0.710> Î± = 0.6, it can be concluded that all items of the statement are reliable. By testing thesimple correlation hypothesis hypothesis there is a relationship between cognitive ability andeffective learning (from changing song lyrics and singing with a correlation value of 0.646, whichmeans that 64.6% of effective learning affects children's cognitive effectiveness while theremaining 35.4% is due to other factor.